Environmental remediation of canga and iron mining waste pile using bee pasture of Baccharis dracunculifolia - Paiva, Anna Syria Aranha; Peixoto, Ricardo André Fiorotti; Moura, Sandra Aparecida Lima de (Revista Brasileira de Ciência, Tecnologia e Inovação, 2024)
Mining is an economic activity known for its significant potential to generate socio-environmental impacts. In the case of iron ore mining in the Iron Quadrangle of Minas Gerais, the areas most frequently affected are typically ferruginous fields, due to vegetation suppression for pit opening and the deposition of waste rocks. Owing to their unique characteristics, these regions exhibit a high degree of endemism, with species adapted to the specific environmental conditions, making them suitable candidates for use in ecological restoration projects. Baccharis dracunculifolia is a native plant with significant potential for inclusion in such projects due to its ability to colonize degraded areas and its interactions with pollinators, such as the honeybee Apis mellifera. Consequently, environmental restoration efforts can be integrated with apicultural production, providing a sustainable alternative for the productive use of previously degraded land. The objective of this research is to identify and compare the physical and chemical properties of soils from iron mining waste piles and canga for potential use in environmental restoration with B. dracunculifolia as a bee pasture. Analyses included particle size distribution, bulk density, moisture content, pH, and chemical composition using X-ray fluorescence (XRF). Results indicated that both environments demonstrated similar properties across all tests, supporting the use of native plants such as B. dracunculifolia in ecological restoration projects. Furthermore, the establishment of bee pastures composed of this species in degraded areas can help diversify the income streams of local communities near mining operations, thereby reducing their dependency on mining activities.